Perancangan Video Protokol Kesehatan New Normal Pada Wedding Organizerohana Enterprise - Yuni Roza; Nia Kurniasih; Pety Fejriati (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2021)
With the Covid 19 pandemic that has hit Indonesia, many companies have suffered serious losses, especially companies engaged in services, one of which is in the world of wedding organizers at Ohana Enterprise. The problem that exists in the company is that there is no educational video about the new normal health protocol during weddings, therefore a health protocol video is needed to be socialized to customers so that it is more conveyed and feels safe during the wedding party. The purpose of this research is to attract prospective customers to use wedding organizer services with Health protocol videos to be more educated so that this health protocol video can educate the wider community and increase sales of wedding organizer service products. The research method used is, the data collection analysis method, SWOT analysis, media design, and the concept of media production (KPM). In which there are stages including Pre Production, Production, and Post Production and Adobe Photoshop CC 2015. This video will be implemented through the Ohana Enterprise youtube channel. Through this video, it is hoped that it can educate prospective customers and attract potential customers to use the wedding organizer services offered by Ohana Enterprise.